Review of the arrowtooth eel genera Dysomma and Dysommina in Taiwan, with the description of a new species (Anguilliformes: Synaphobranchidae: Ilyophinae) - Ho, Hsuan-Ching; Smith, David G.; Tighe, Kenneth A. (Zootaxa, 2015)
Species of the synaphobranchid eel genera Dysomma and Dysommina from Taiwan are reviewed. A total of eight species in Dysomma and one species in Dysommina are recognized. A new Dysomma species is described based on four specimens collected from off Taiwan. It differs from its Taiwanese congeners in having 137–139 total vertebrae, pectoral fin well-developed, 2 intermaxillary teeth, 4 compound teeth on vomer, 40–48 total lateral-line pores, the last at about middle of body, and a uniform brownish color. A key to all species in these two genera in Taiwan is provided.